Aspects of cognition that impact aging‐in‐place and long‐term care planning. Issue 9 (20th June 2022) - Lindquist, Lee A.; Miller‐Winder, Amber P.; Schierer, Allison; Murawski, Alaine; Opsasnick, Lauren; Curtis, Laura M.; Kim, Kwang‐Youn; Ramirez‐Zohfeld, Vanessa
Abstract: Background: Older adults frequently defer decisions about their aging‐in‐place/long‐term care (AIP‐LTC) needs. As a result, when older adults experience worsening Alzheimer's disease, family members/friends become surrogate decision makers. We sought to understand what aspects of cognition impact older adult AIP‐LTC planning. Methods: As part of the PlanYourLifespan (PYL)‐LitCog study, we longitudinally examined AIP‐LTC decision‐making among a cohort (LitCog) of community‐based older adults (65 years and older) recruited from hospital‐associated primary care clinics in Chicago, Illinois, with extensive cognitive testing. PlanYourLifespan.org (PYL) is an evidence‐based online intervention that facilitates AIP‐LTC planning. Subjects underwent baseline testing, received the PYL online intervention, and then were surveyed at 1, 6, and 12 months about AIP‐LTC decision‐making. Cross‐sectional logistic regression analysis was conducted examining cognitive variables that impacted AIP‐LTC decision‐making. Results: Of the 293 older adults interviewed (mean age 73.0 years, 40.4% non‐White), subjects were more likely to have made AIP‐LTC decisions if they had adequate inductive reasoning (ETS letter sets total—OR = 1.14 (95% CI = 1.03–1.27; p < 0.05)) and adequate working memory (size judgment span total—OR = 1.76 (95% CI = 1.13–2.73; p < 0.05)). There were no differences in decision‐making observed in verbal abilities, long‐term memory, or processing speed. All analyses were adjusted for participant gender, race, age, and decision‐making response at baseline. Conclusion: Inductive reasoning and working memory are critical to AIP‐LTC decision‐making. Screening routinely for these specific cognitive domains is important in targeting and helping older adults prepare in time for their future AIP‐LTC needs.